Pengaruh Efikasi Diri, Persepsi Kesejahteraan Guru, dan Pengalaman Pengenalan Lapangan Persekolahan (PLP) terhadap Minat menjadi Guru pada Mahasiswa Kependidikan Angkatan 2021 Universitas Negeri Semarang - Maharani, Dira; Pitaloka, Lola (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the influence of self-efficacy, perceptions of teacher welfare, and Field Experience Program (PLP) participation on the interest in becoming a teacher among 2021 education students at Universitas Negeri Semarang. The background of this research is based on the low interest of students in pursuing a teaching career, despite the growing demand for teachers in Indonesia each year. This study employs a quantitative approach with a causal associative and explanatory research design. The population consists of education students from the 2021 cohort at UNNES who have completed the PLP, with a sample of 366 respondents selected using proportional random sampling. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability. Data analysis techniques included classical assumption testing, multiple linear regression analysis, and the coefficient of determination test using SPSS version 25. The findings of this study are expected to contribute to teacher education institutions (LPTK) in formulating strategies to enhance students' interest in becoming teachers by strengthening self-efficacy, perceptions of teacher welfare, and optimizing PLP experiences.